Analisis Nilai Pendidikan Karakter dalam Fabel Jerman Pada Kumpulan Dongeng Brüder Grimm - Ninda Ninda; Syamsu Rijal; Hasmawati Hasmawati (Universitas Negeri Makassar, 2022)
Abstract. This research is descriptive qualitative research. This research aims to describe the value of character education contained in the three German fables in the collection of Brüder Grimm tales and their relevance in learning German at school. Data sources of this research were primary and secondary data. Data collecting, the researcher used reading and note-taking technique. The data obtained were then analyzed using the analysis of the Miles and Huberman model. The findings show that the values of character education contained in these three fables are obedient, committed, not easy to give up, loving each other, cooperation, brave, not greedy, creative, helping, hardworking, caring for others, loyal, and empathy. These values are relevant to the value of character education to be realized in the cultural and character education of the Indonesian nation, so that the three fables can be one of the choices of teaching materials in learning German in schools.Keywords: Fabel, Brüder Grimm, Character Education